Pengaruh Terpaan Iklan Layanan Masyarakat “Don’t Know? Kasih No!” oleh BCA Terhadap Sikap Pengguna Twitter/X - Joel Gerald Halomoan Hutauruk; Anter Venus; Putri Trulline (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2025)
With the existence of social media, the distribution of public service advertisement videos has become easier. However, the rampant cases of phishing in society lately have the potential to harm users of online banking services. The purpose of this study is to determine the effect of exposure to public service advertisements on the attitudes of Twitter / X users. This study uses a quantitative approach. The choice of research method that will be used is the quantitative causality method. This study will use X / Twitter users who have watched the public service advertisement video "Don't Know? Kasih No!" by Bank Central Indonesia. The results of this study are that the variables product / message thoughts, source oriented thoughts, and ad execution thoughts simultaneously have a positive and significant influence on the formation of attitudes of Twitter / X users. It can be concluded that these three variables help in the process of receiving messages and forming audience attitudes when watching the public service advertisement video "Don't Know? Kasih No!"